2019
DOI: 10.2478/revecp-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of financial development on income inequality in Turkey: An estimate of the Greenwood-Jovanovic hypothesis

Abstract: This paper is the first to examine the linear and nonlinear effect of financial development on income inequality in Turkey over the period of 1980-2013. Financial development is represented by disaggregated and aggregated indicators. In this way, the effects of various financial indicators on income inequality are explained. Maki (2012) structural breaks co-integration test, and Stock and Watson (1993) dynamic ordinary least squares (DOLS) methods are followed for empirical analysis. Finally, the fully modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…In Model 2 and Model 3 too, where control variables were integrated, identical results were obtained. Results collected from Models 1, 2 and 3 confirmed that between FD and income inequality an inverted U relationship existed, and these findings are aligned with studies conducted by Clarke et al (2003Clarke et al ( , 2007, Rehman et al (2008), Batuo et al (2010), Kim and Lin (2011), Rötheli (2011), Nikoloski (2012, Shahbaz et al (2014), Koçak and Uzay (2019).…”
Section: The Modelssupporting
confidence: 87%
See 3 more Smart Citations
“…In Model 2 and Model 3 too, where control variables were integrated, identical results were obtained. Results collected from Models 1, 2 and 3 confirmed that between FD and income inequality an inverted U relationship existed, and these findings are aligned with studies conducted by Clarke et al (2003Clarke et al ( , 2007, Rehman et al (2008), Batuo et al (2010), Kim and Lin (2011), Rötheli (2011), Nikoloski (2012, Shahbaz et al (2014), Koçak and Uzay (2019).…”
Section: The Modelssupporting
confidence: 87%
“…A different hypothesis suggests that financial development would expand income inequality (positive linearity), the widening hypothesis. This hypothesis puts forth that in countries with a weak financial structure, those wealthy and with good connections benefited more from the financial development compared to the poor, and as expected, financial development would fail to contract income inequality (Koçak and Uzay, 2019). Unlike rich people who can provide their assets as collateral in return for any purchased service, poor citizens would have no collateral to offer to financial intermediaries and as a consequence, they would not sufficiently benefit from the provided services.…”
Section: Motivationmentioning
confidence: 93%
See 2 more Smart Citations
“…This U-shape form is similar to that found by Kuznets (1955), but the latter describes inequality in relation to GDP per capita rather than financial development. The Ushape hypothesis is widely accepted (Koçak & Uzay, 2019;Destek et al, 2020;Kavya & Shijin, 2020). However, Piketty (2014) disagreed, arguing that the gap of earnings would never converge as long as the return from assets continues to grow higher than economic (income) growth.…”
Section: Introductionmentioning
confidence: 99%